PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT TERHADAP PEMAHAMAN KONSEP PESERTA DIDIK PADA PEMBELAJARAN FISIKA - agustina agustina agustina; Misdalina Misdalina; Lefudin Lefudin (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The formulation of the problem in this study is the effect of the Cooperative Learning model of the types of Team Games Tournament on the ability of students to understand the concept of physics learning in class X in SMK PGRI 2 Palembang. This study aims to determine whether or not there is an influence of the cooperative learning model of type of Team Games Tournament (TGT) on the ability of students to understand the concepts of physics in class X learning at SMK PGRI 2 Palembang. The research method used is the Experimental Design method, the category of Posstest-Only Control Design. in this design often used in research experiments with data collection technigues obtained using tests, and documentation.The average value of student learning outcomes in the experimental class can be categorized as good at 78.47 by using the cooperative games tournament type (TGT) Model, while the average value of the learning outcomes of the control class by not using the model cooperative Team Type Tournament games can be categorized enough with the average student learning outcomes is 63.05. Based on calculations t arithmetic > t table = 7.105 > 1.667 ie t arithmetic = 7.105 and t table = 1.667 then accept the hypothesis (ha) which means ” There is an influence of the cooperative learning model Team Games Tournament type (TGT) on the ability of students to understand the concept of learning physics in class X in SMK PGRI 2 Palembang.